ANALISIS PENGGUNAAN TABUNGAN MOBILE BANKING MENURUT PERSPEKTIF MAQASHID SYARIAH (HIFZ AL MAL) - Elsa Indriani; Asyari (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
The development of digital technology has encouraged banks to provide mobile banking services as a practical and efficient way to conduct transactions. Due to its convenience and flexibility, this service is often used by students. However, the use of mobile banking also needs to be considered from a Sharia perspective, especially in terms of asset protection (hifz al-mal), which is one of the objectives of Maqashid Sharia. The purpose of this study is to analyze the use of mobile banking from the perspective of Maqashid Sharia (hifz al-mal) among students in the Sharia Banking Study Program at UIN Sjech M. Djamil Djambek Bukittinggi. This study uses a qualitative descriptive approach with data collection techniques using documentation and interviews. The findings show that the use of mobile banking is influenced by information transparency, transaction security, and risk management. However, asset protection has not reached its optimal condition because the level of literacy and digital awareness of users still has a negative impact. Therefore, it is necessary to increase user understanding and awareness so that the goal of hifz al-mal can be achieved more comprehensively.